Soil surface evaporation studies on the Glen/Bonheim ecotope - Nhlabatsi, Nhlonipho Nhlanhla (University of the Free State, 2010)
The biggest challenge in semi-arid areas is finding ways of reducing the major unproductive water loss: evaporation from the soil surface. A large number of subsistence farmers east of Bloemfontein, in and around Thaba’Nchu in the Free State Province of South Africa occupy about 11 000 ha of land. The economic potential of this communal land still needs to be unlocked and the natural resource base is critical for this endeavour. However, the prevalence of clay and duplex soils is a major constrain towards improving food security in this area. Poor soil water regimes resulting from prolific runoff and evaporation losses is one of the reasons especially when conventional tillage is used. It was therefore hypothesized that by quantifying soil surfaces evaporation (Es); characterizing of the soil hydraulic properties and understanding the effect of temperature on mulch type and coverage of the Bonheim (Bo) soil can contribute to the improvement of the infield rainwater harvesting (IRWH) system and fill a gap in knowledge under South African conditions that is in terms of promoting water storage capacity and minimizing Es for better crop yields. The ECH2O-TE probes used in this study were calibrated to measure soil water content ( ) and temperature (T). The evaporative desorption procedure (EDP) of Van der Westhuizen (2009) for coir was modified to calibrate probes in undisturbed soils. The probes were evaluated against measured volumetric soil water content (mm mm-1) on their accuracy, precision and repeatability to measure soil water content in the 26oC treatment (Chapter 2). Most of the laboratory derived equations had RMSE close to zero, on average at 0.003 mm mm-1 and precision (R2) ranged between 93 and 99% and accuracies up to 96%. These probes were found to be sensitive to soil temperature changes in the measurement of water content. Under wet to dry soil conditions about 48, 62 and 34% errors were obtained for the A, B and C-horizons, respectively and therefore temperature compensated equations had to be developed in Chapter 3. Temperature compensated equations predicted soil water content measurements with an accuracy, precision and repeatability at 99, 99 and 95%, respectively. Manufacturer’s generic equation tended to over predict soil water content measurements and lacked accuracy with errors ±40% and repeatability. Chapter 4 investigated how mulch type and percentage cover influenced temperature above and below the soil surface. First: results indicated that mulch did not influence air temperature at an elevation of 160 mm above the soil surface. Secondly: percentage coverage affected soil temperature up to 450 mm, and thirdly: the 100% reed mulch cover treatment was recommended for farmers in order to minimise evaporation especially under semi-arid conditions where normally the evaporative demand exceeds supply. Chapter 5 on the other hand profiled and characterized the hydraulic properties of the Bo soil for the A, B and C-horizons. Soil pores were separated into structural and textural pore classes for each of the horizons that were identified for the three master horizon of the Bonheim soil using a method first used in this study known as the “in situ internal drainage” (ISID) method. The drained upper limit (DUL) for each horizon was determined using the ISID method and were found to be associated with micro pore class. The structural pores of the three horizons were found to be associated with low suctions and that they allowed water to flow at rates between 1-20 mm hr-1. The transitional pore class (Meso pores) conducted water at rates between 3-12 mm hr-1 and micro pores between 3-10 mm hr-1. Five methods were used to estimate evaporation (Es) during three Es drying cycles (Chapter 6) and these estimations were compared to a weighing lysimeter [Es(lys)] measurements in order to evaluate their accuracy in the measurement of Es, using Willmot test statistics for paired values. The field hydraulic method had a good performance with an average D-index value of 0.60 in all the three drying cycles selected and thus estimated Es closer to Es(lys) hence it was recommended for use in estimating Es for Bo soils.
Thesis (Ph.D. (Soil, Crop and Climate Sciences))--University of the Free State, 2010
Keywords: ECH2O-TE probe; Soil water content; Calibration procedure; Temperature; Soil; Mulch; Reed; Hydraulic conductivity; Drainage; Evaporation; Water -- Thermal properties; Heat -- Transmission; Evaporation -- Soil moisture -- Measurement -- Instruments